Pengaruh Produksi, Indeks Harga Perdagangan Besar dan Kurs Dollar Amerika Serikat Terhadap Ekspor Kayu Lapis di Indonesia - Putra, A.A Putu Yudha; Kesumajaya, I Wayan Wita (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 8. Agustus 2017(pp.1395-1627), 2017)
The aims of this research are determine the effect production, wholesale price index and US dollar exchange rate dollars to export of the plywood on indonesia simultaneous or partial and to know the independent variables were the dominant influence independent the on Indonesia's plywood exports. This study used secondary data and used multiple linear analysis are processed using SPSS. Based on the result, (1) production, the wholesale price index and the US dollar exchange rate have a significant effect simultaneous on plywood exports, Partial (2) Production significant to export plywood , (3) wholesale price index have a significant effect on exports of plywood, (4) the United States dollar exchange rate has not significant effect on exports of plywood. (5) The most dominant variable is the production of plywood. To realize it needed cooperation with the w ith the government to facilitate the development of the industry sector special industry plywood .
Keywords: ekspor; produksi; indeks harga perdagangan besar; kurs dollar Amerika Serikat